1996
DOI: 10.1002/(sici)1097-0215(19960503)66:3<404::aid-ijc23>3.0.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quercetin on the genotoxic potential of cisplatin

Abstract: The natural product flavonoid quercetin has been shown to sensitise cells to the cytotoxic potential of cisplatin. Both cisplatin and quercetin are genotoxicants. As quercetin is curnntly in clinical trial as a cytotoxicMt-sensitising agent, we wanted to elucidate whether it affects the genotoxicity associated with cisplatin. The genotoxic potential of both agents alone and in combination was studied in Solmonello typhlmurium strains TA 98, TA 100 and TA 102 and by assessment of unscheduled DNA synthesis (UDS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…The interest in quercetin for therapeutics application is spurred by its ability to sensitize cells to the cytotoxic effects of platinum-containing drugs [16]. However, limited research is available on the role of quercetin in NPC and potentiation is seldom defined as additive or synergistic.…”
Section: Discussionmentioning
confidence: 99%
“…The interest in quercetin for therapeutics application is spurred by its ability to sensitize cells to the cytotoxic effects of platinum-containing drugs [16]. However, limited research is available on the role of quercetin in NPC and potentiation is seldom defined as additive or synergistic.…”
Section: Discussionmentioning
confidence: 99%
“…Cross et al [42] have shown that cisplatin was mutagenic using the Ames test, suggesting that using cisplatin could lead to an increased risk of secondary malignancies. They conclude that normal cells in patients undergoing treatment with cisplatin were at an increased risk of genotoxicity and that this must be taken into consideration when deciding on cancer treatment with this agent.…”
Section: Discussionmentioning
confidence: 99%
“…The exact cause of the syndromes 3-5 remains unknown, but a range of chemical constituents of Pteridium (ptaquilosides, quercetin and shikimic acid) has been implicated (Evans 1976a;Smith et al 2000). Chemicals in Pteridium, known to have carcinogenic, cytotoxic, mutagenic, tumorigenic and teratogenic activity, can induce apoptosis and symptoms were radiomimetic (Evans 1976a(Evans , 1986Santos et al 1992;Cross et al 1996;Ngumuo & Jones 1996;Rzymowska et al 1999;Simán et al 2000). Ptaquiloside, for example, has been shown to have a DNA-binding capacity and cleaves DNA (Kigoshi et al 1992).…”
Section: Mammalsmentioning
confidence: 99%
“…Chemicals in Pteridium , known to have carcinogenic, cytotoxic, mutagenic, tumorigenic and teratogenic activity, can induce apoptosis and symptoms were radiomimetic (Evans 1976a, 1986; Santos et al . 1992; Cross et al . 1996; Ngumuo & Jones 1996; Rzymowska et al .…”
Section: Herbivory and Diseasementioning
confidence: 99%